2005
DOI: 10.1111/j.1528-1167.2005.64504.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Thalamic Injury Associated with Epilepsy and Continuous Spike–Wave during Slow Sleep

Abstract: Summary:Purpose: Mechanisms inducing continuous spikewave during slow sleep (CSWS) in encephalopathy with electrical status epilepticus during sleep are still unclear. Recently, some sporadic cases with early thalamic injury associated with CSWS have been reported. The aim of the study was to investigate in a population of patients with an early thalamic injury the presence of an activation of paroxysmal activities during sleep, their characteristics, and possible relations to neuroimaging and neuropsychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
111
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(132 citation statements)
references
References 19 publications
11
111
0
10
Order By: Relevance
“…Раннее органическое поражение таламуса (обычно вследствие дисциркуляторных нарушений в перина-тальном периоде) с резким усилением гиперсинхрони-зации эпилептиформных разрядов во сне может быть одной из причин развития ЭЭСМ [27,44].…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified
See 1 more Smart Citation
“…Раннее органическое поражение таламуса (обычно вследствие дисциркуляторных нарушений в перина-тальном периоде) с резким усилением гиперсинхрони-зации эпилептиформных разрядов во сне может быть одной из причин развития ЭЭСМ [27,44].…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified
“…Также важную роль в генезе ПЭМС на ЭЭГ имеет аномальная возбудимость нейрональных сетей в систе-ме кора-таламус-кора [48]. Это подтверждается случа-ями возникновения ЭЭСМ при раннем органическом (перинатальном) повреждении таламуса [27,44].…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified
“…Patients with shunted hydrocephalus, represented approximately 30% of cases of reported by Veggiotti et al (1999) and by Caraballo et al (2008). Early thalamic lesions seemed to be also strongly associated with sleep-enhanced epileptiform discharges (Monteiro et al, 2001;Kelemen et al, 2006;Guzzetta et al, 2005;Andrade-Machado et al, 2012;Sánchez Fernán-dez et al, 2012;Loddenkemper et al, 2012;Quigg and Noachtar, 2012). Hegyi et al, (2014) in their study of 33 patients with ESES attending the Bethesda Hospital, Budapest, identified sleep EEGs in 171 records, on average 5/patient and wake recordings in 492 records, on average 15/patient).…”
Section: History and Etiology Of Esesmentioning
confidence: 99%
“…From the etiological point of view there were 15 patients without and 18 patients with structural abnormalities. In the Guzzetta et al (2005) study of the 32 patients identified, all but 3 patients had early thalamic lesion ESES like activation, while in the Bethesda study of the 32 patients with ESES only 4 patients had thalamic lesions (among them an isolated thalamic lesion was present in only one patient).…”
Section: History and Etiology Of Esesmentioning
confidence: 99%
“…The role of MEG remains to be explored in this entity. Kelemen et al [17] reported three patients with CSWS secondary to destructive lesions in the thalamus [14], and CSWS development was often observed in patients with a thalamic lesion, indicative of thalamo-cortical dysfunction with an epileptic 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Shiraishi et al, page 18 network [15,16]. ESM can be efficacious for seizures In ABPE patients, especially for ENM [6].…”
Section: Meg Localized Spike Dipoles In Csws Of Abpementioning
confidence: 99%